2020
DOI: 10.1108/rpj-07-2019-0205
|View full text |Cite
|
Sign up to set email alerts
|

Multi-material 3D printed hydraulic actuator for medical robots

Abstract: Purpose This study aims to investigate the potential of using polymer multi-material additive manufacturing (MMAM) to produce miniature hydraulic piston actuators combining rigid structures and flexible seals. Such actuators offer great potential for medical robots in X-ray and magnetic resonance environments, where conventional piston actuators cannot be used because of safety issues caused by metal components. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…The capacity to produce multimaterial components was exploited to design each piston as a single part, with a hollow shape at the tip. It was observed [18] this creates an adaptive sealing effect: friction between the piston and the bore is reduced for low fluid pressure, while high fluid pressure increases the friction to avoid leakage (Fig. ??).…”
Section: Design Of Hydraulic Cylindersmentioning
confidence: 99%
See 1 more Smart Citation
“…The capacity to produce multimaterial components was exploited to design each piston as a single part, with a hollow shape at the tip. It was observed [18] this creates an adaptive sealing effect: friction between the piston and the bore is reduced for low fluid pressure, while high fluid pressure increases the friction to avoid leakage (Fig. ??).…”
Section: Design Of Hydraulic Cylindersmentioning
confidence: 99%
“…There are still limits to the proposed hydraulic-based actuated joint in its current implementation. First, the use of Polyjet process as considered here with TangoBlack plus material was observed to suffer from material degradation for long-term uses [18]. Further process development would help to have functional systems with large endurance.…”
Section: Characterization Of the Componentmentioning
confidence: 99%
“…The valves are a very simple three-piece assembly with an assembled diameter of 3 mm. Multi material additive manufacturing has been used to print hydraulic actuators with integrated seals safe for medical applications [15]. These examples show how 3D printing is being utilized to produce very low-pressure hydraulic components in ways not possible by traditional manufacturing methods.…”
Section: P Cmentioning
confidence: 99%
“…However, for direct AM of complex multi-material components, only a few technologies are available. The most wide-spread commercial option is the PolyJet (PJ) process (Siegfarth et al , 2020), in which objects of desired shapes are accumulated from droplets of acrylate-based photocurable ink that are deposited via piezo nozzles and cured by infrared light. Kundera and Bochnia (2014) fabricated O-ring seals using PJ technology and found that, although the seals were usable, they exhibited complex time-dependent mechanical behavior.…”
Section: Introductionmentioning
confidence: 99%